A systematic review on synthesis and anticancer activity of podophyllotoxin from podophyllum peltatum L - Mythili Arthanari (International Journal of Pharma and Bio Sciences, 2020)
The objective of this present review is to give a brief view about the use, synthesis and analysis of anticancer activity of podophyllo toxin from podophyllum peltatum L. PubMed, Elsevier, Google scholar search engine is utilized for collecting literatures which have detailed study of role, synthesis and potential therapeutic effects of podophyllotoxin from podophyllum peltatum L. Podophyllotoxin is an important chemical compound which is majorly obtained from plant source of podophyllum peltatum L and podophyllum hexandrum R .Podophyllum peltatum L is only plant have podophyllotoxins of around 68 percentage obtained from may to june at flowering stage. Phenyl alanine, cinnamic acid, ferulic acid were involved in the synthesis of podophyllotoxin. It binds and damages microtubule polymerization which leads to cell cycle arrest and concern DNA damage occurrs. Endoplasmic reticulum stress and autophagy was induced due to cell death by podophyllotoxin. Several investigations have been performed for biosynthesis, synthesis and anticancer activity according to literature. This review of research is an overview of anticancer activity of podophyllotoxin from Podophyllum peltatum L. The research will find an alternative way to satisfy pharmaceutical demand of podophyllotoxin.